The Role of Student Management in Implementing Religious Development Activities at MTs Nurul Islam Kota Kediri - Latifah, Umi; Orwela, Citra (Indonesian Journal of Multidisciplinary Educational Research, 2024)
Religious behavior is the most crucial point that serves as the foundation for equipping students with attitudes and behaviors relevant to daily life. Therefore, schools must be able to demonstrate good and religious behavior to students. Religious behavior development is the process of shaping behavior, morality, and character for students as a preparation for both the present and future. Schools must effectively manage their students to produce individuals who meet the expected and aspired standards. This study uses a descriptive qualitative approach to describe the management of student behavior in religious development at MTs Nurul Islam in Kediri City. The activities for developing religious behavior at MTs Nurul Islam in Kediri City include planning, organizing, implementation, and supervision. Habitual activities are carried out through reading Surah Yasin, reading Surah Al-Kahf, Istighosah, Tahlil, performing Dhuha prayers in congregation, celebrating major religious holidays together, and participating in the Ramadan boarding activities. These findings suggest that students become accustomed to engaging in worship activities, which directly influences their character development for the better